2014
DOI: 10.1111/acps.12245
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of controlled interventions to reduce overweight and obesity in people with schizophrenia

Abstract: The included studies indicate that the interventions reduced weight and improved physical health parameters in patients with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 46 publications
0
57
0
1
Order By: Relevance
“…Half of all patients are overweight (Mitchell et al, 2013) with a risk of severe negative health consequences (Harris & Barraclough, 1998;McEvoy et al, 2005). Interventions can effectively reduce overweight in patients with schizophrenia (Hjorth, Davidsen, Kilian, & Skrubbeltrang, 2014). Both high body mass index (BMI) and increased waist circumference have been linked to lower health-related QOL (HR-QOL; Ware, 2005) in the general population (Han, Tijhuis, Lean, & Seidell, 1998;Jia & Lubetkin, 2005).A similar association in patients with schizophrenia seems conceivable.…”
Section: Quality Of Life and Clinical Characteristics In A Nonselectementioning
confidence: 99%
“…Half of all patients are overweight (Mitchell et al, 2013) with a risk of severe negative health consequences (Harris & Barraclough, 1998;McEvoy et al, 2005). Interventions can effectively reduce overweight in patients with schizophrenia (Hjorth, Davidsen, Kilian, & Skrubbeltrang, 2014). Both high body mass index (BMI) and increased waist circumference have been linked to lower health-related QOL (HR-QOL; Ware, 2005) in the general population (Han, Tijhuis, Lean, & Seidell, 1998;Jia & Lubetkin, 2005).A similar association in patients with schizophrenia seems conceivable.…”
Section: Quality Of Life and Clinical Characteristics In A Nonselectementioning
confidence: 99%
“…Indeed, fitness may be more important than overweight or obesity for cardiovascular risk 4. Such interventions are feasible although they will likely need to be highly structured, with early and intensive support initially and offering reduced but continued support over time (if not indefinitely) 5. For some individuals with schizophrenia, however, behavioural interventions may not be appropriate due to significant impairment in functioning and insight.…”
Section: Do These Results Change Your Practices and Why?mentioning
confidence: 99%
“…It seems that physical health of individuals with mental illness improves when mental health nurses promote patients to improve their physical health. For example, Hjorth et al . systematically investigated interventional studies that were conducted to reduce weight and obesity in schizophrenic patients.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the interventions of physical health promotion for patients could improve the physical health parameters of patients (BMI, weight etc.) and promote patients to lose weight . Various interventional studies have been conducted to prevent weight gain and to promote healthy lifestyles in individuals with mental illness, and it has been emphasized that the interventions provided a reduction in BMI of patients …”
Section: Introductionmentioning
confidence: 99%